ANALISIS EFISIENSI PEMASARAN IKAN PATIN (Pangasius Sp) DI CINDAI ALUS KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Diana Haryanti; Emmy Sri Mahreda; Rina Mustika (Fish Scientiae, 2019)
There are problems happening in the marketing system of fresh catfish in Cindai Alus in which the profits received by merchants or middlemen are higher than retailers.The share or benefits received by fish farmers in Cindai Alus are higher than merchants and retailers. This share is as the selling price of fresh catfish from the farmers to the collectors and then to be sold again to the retailers, and finally to the consumers with a higher price.This study is aimed at finding out the marketing channels of fresh fish, especially catfish (Pangasius sp) in Cindai Alus area, finding out the marketing agents either as producers or consumers, determining the differences in the marginal level of marketing and profitability of each agents as well as factors affecting the margin, finding out the share price received by the producers from the consumers price in different marketing channels, and finding out the structure, behavior and market performance of catfish (Pangasius sp) in Cindai Alus.This study applied survey and interview as methods of data analysis. The data collected included primary data, i.e. data from the fish farmer the main source which obtained through a structured interview (with questionnaire), as well as secondary data obtained from various sources, such as the results from other research, literature study and information from related institutions relevant to the study.The results showed that the pattern of marketing channels of fresh catfish (Pangasius sp) from the farmers to the final consumers in Cindai Alus consists of 4 patterns and marketing participants consist of manufacturers, merchants from local orfrom other regions, and retailers. In addition, the share percentage received by the fish farmers are efficient by 87.26%, and the marketing system of fresh catfish in Cindai Alusis considered as imperfect competition structure or oligopsony in which the amount of sellers are bigger than the buyers.